On the Supportive Role of the Warnke Method in Improving the Phonological Competence of a Bilingual Girl - Ewa Brzdęk; Janusz Brzdęk (MDPI AG, 2021)
It is known that bilingualism may cause some specific problems with the articulation of sounds and errors in reading and writing when acquiring linguistic skills. The paper presents the results and conclusions related to the use of the Warnke method in improving the phonological competence of a bilingual girl aged seven, which learned two languages simultaneously (Polish and Italian) in her family environment. The case study method was used. The main objective was to assess the effectiveness of the first stage of the Warnke method in improving reading and writing skills in a bilingual child. The Warnke method focuses primarily on the diagnosis and training of the phonological competence and was based on the following assumptions: (a) the automation of hearing, vision, and motor functions can be improved at the level of brain activity; (b) the development and automation of phonological analysis and synthesis are based on the cooperation of the brain hemispheres. The preliminary and final results of the diagnosis obtained for basic brain functions (visual, motor, and auditory) and the level of literacy skills were analyzed and compared. The reading and writing abilities, before and after training with the Warnke method, were assessed using the symptomatic tests. The obtained results showed that during and after training with the method, there was noticeable progress in eight basic functions (visual, motor and auditory). Improvement was also seen in the following areas: knowledge of letters; pairing phonemes with letters; technique, speed, and fluency of reading and writing. The quality of reading and writing was verified and confirmed by symptomatic tests. The conducted study suggests that the observed learning disabilities were caused by deficits in the central processing functions, which resulted in a lower level of phonological skills.